Epileptic Syndromes and Photosensitive Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
The clinical features of different types of photic-induced seizures and epileptic syndromes characterized by visual sensitivity are reviewed from the University of Pisa, Italy, and Centre St Paul, Marseille, France.